2022
DOI: 10.4103/ajts.ajts_73_21
|View full text |Cite
|
Sign up to set email alerts
|

Illustration: Thromboelastography – A useful tool to monitor COVID-19-associated coagulopathy

Abstract: COVID 19 is caused by Severe Acute Respiratory Syndrome Corona Virus-2 which results in wide range of manifestations. Systemic hypercoagulation is a typical feature of COVID-19. We present a case of COVID-19 in whom TEG was performed on admission and hypercoagulability was diagnosed and hence patient was started on Enoxaparin sodium 6000 IU twice daily. TEG was repeated after 5 days which showed normal coagulation status and the patient was discharged without any thrombotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…They found that changes in the ROTEM variables were correlated with disease severity, and that the disease course followed changes seen in ROTEM. This is in line with other studies that used similar methods, including thromboelastography, which were able to detect and diagnose hypercoagulability in patients with COVID-19, enabling relevant treatment [ 11 ].…”
Section: Group 101: Clinical Problemssupporting
confidence: 88%
“…They found that changes in the ROTEM variables were correlated with disease severity, and that the disease course followed changes seen in ROTEM. This is in line with other studies that used similar methods, including thromboelastography, which were able to detect and diagnose hypercoagulability in patients with COVID-19, enabling relevant treatment [ 11 ].…”
Section: Group 101: Clinical Problemssupporting
confidence: 88%